Identification of FBN1 gene mutations in Ukrainian Marfan syndrome patients - ZHURAYEV, RUSTAM (Genet Res (Camb), 2016)
Marfan syndrome is an autosomal dominant connective tissue disorder, predominantly affecting the ocular, skeletal and cardiovascular systems. Here, we present the results of the first genetic testing in 40 Ukrainian Marfan (-like) patients and 10 relatives. We applied a targeted next generation sequencing panel comprising FBN1 and 13 thoracic aortic aneurysm genes. We identified 27 causal mutations in FBN1, obtaining a mutation yield of 67·5%. A significant difference in age at aortic surgery between mutation positive and negative patients was observed. Thus, we conclude that genetic testing is important to identify patients at higher risk for developing life-threatening cardiovascular complications.